A social network analysis of large-scale wildlife seizures made at US ports of entry - Pires, Stephen F. (Deviant behavior, 2023)
The United States is among the largest markets of both legal and illegal wildlife in the world. Prior studies of wildlife seized at US ports of entry have demonstrated that a small number of flora and fauna species account for a disproportionate share of illicit wildlife seizures and that a select number of entry ports and export countries account for the large majority of these seizures. However, the distributional flow of wildlife entering the US - the patterns of where a particular wildlife originates and the port of entry it arrives at - remains unclear. Using a social network analysis to model 31,270 large-scale trafficking incidents between 2003 and 2012, we found that removing five ports from the network would disrupt over 66% of the illegal wildlife trade by each major mode of transportation (air cargo, mail, personal baggage, ocean cargo). Further, certain ports have emerged as important seizure hubs regardless of transportation modes, such as San Francisco and Los Angeles, while other US entry ports are highly dense and seized most illicit wildlife specifically by one transportation mode. On the exporter side, China, Mexico, and Southeast Asia had an outsized effect on network clusters and should be targeted for network fragmentation and anti-trafficking education campaigns.